Tuberculosis Infection in a Patient Treated With Nivolumab for Non-small Cell Lung Cancer: Case Report and Literature Review - van Eeden, Ronwyn; Rapoport, Bernardo L.; Smit, Teresa; Anderson, Ronald (Frontiers in Oncology, 2019)
Nivolumab (PD-1 blocker) and other immune checkpoint inhibitors are used primarily to promote reactivation of anti-tumor immunity. However, due to their generalized immunorestorative properties, these agents may also trigger an unusual spectrum of side-effects termed immune-related adverse events. In the case of the lung, pulmonary infiltrates in patients treated with the anti-PD-1 inhibitors, nivolumab or pembrolizumab,, especially patients with non-small cell lung cancer, can result from immune-related pneumonitis, which, until fairly recently was believed to be of non-infective origin. This, in turn, may result in progression and pseudo-progression of disease. An increasing body of evidence has, however, identified pulmonary tuberculosis as an additional type of anti-PD-1 therapy-associated, immune-related adverse event, seemingly as a consequence of excessive reactivation of immune responsiveness to latent Mycobacterium tuberculosis infection. The current case report describes a 56-year old Caucasian female who presented with microbiologically-confirmed tuberculosis infection while on nivolumab therapy for non-small cell lung cancer. Notably, the patient, seemingly the first described from the African Continent, had not received immunosuppressive therapy prior to the diagnosis of tuberculosis.